Different assessment tools to detect sarcopenia in patients with Parkinson's disease - Valent, Dora; Peball, Marina; Krismer, Florian; Lanbach, Anna; Zemann, Sophie; Horlings, Corinne; Poewe, Werner; Seppi, Klaus (Frontiers in Neurology, 2022)
Introduction Sarcopenia and Parkinson's disease are closely related diseases of the elderly population leading to progressive disability and nursing-dependent care. Objective The aim of this study was to estimate the prevalence of sarcopenia in PD patients with three different approaches: (1) the screening tool SARC-F, (2) EWGSOP-1 criteria, and (3) EWGSOP-2 criteria. Moreover, we aimed to evaluate the diagnostic accuracy of the screening tool SARC-F to detect sarcopenia according to the updated EWGSOP-2 criteria. Methods Eighty-one patients with Parkinson's disease aged 65 years and above were interviewed in a cross-sectional study at a tertiary referral center. All patients were screened with the SARC-F questionnaire and were evaluated for motor and non-motor symptoms, exercise, quality of life, and frailty. Muscle mass was assessed with bioelectrical impedance analysis, handgrip strength with a dynamometer, and gait speed was assessed with the 8-m walk test. EWGSOP-2 criteria were considered the gold standard to diagnose sarcopenia in our study. Results Eighty-one patients were evaluated (mean age: 73.82; SD 5.30). The prevalence of sarcopenia was 28.4% according to the EWGSOP-2 criteria. The concordance between EWGSOP-2 and EWGSOP-1 was poor (weighted kappa of 0.361[95% 0.164–0.557]). The sensitivity of the SARC-F screening test for detecting sarcopenia was 60.9%. The corresponding AUC in the ROC curve analysis showed 0.598 (0.462, 0.734 CI). The item assessing strength was found to have the highest sensitivity (69.6%). Conclusion Sarcopenia prevalence in patients with PD in Tirol, Austria is higher with EWGSOP-1 criteria compared to EWGSOP-2 criteria. The sensitivity and specificity of the SARC-F scale to detect sarcopenia in this population are poor.